Age-Related Utilization of Thrombus Aspiration in Patients With ST-Segment Elevation Myocardial Infarction: Findings From the Improving Care for Cardiovascular Disease in China Project - Qu, Yang-Yang; Zhang, Xiao-Guo; Ju, Cheng-Wei; Su, Ya-Min; Zhang, Rui; Zuo, Wen-Jie; Ji, Zhen-Jun; Chen, Li-Juan; Ma, Gen-Shan (Frontiers in Cardiovascular Medicine, 2022)
Background: There are some controversies on the utilization and benefits of thrombus aspiration in patients with ST-segment elevation myocardial infarction (STEMI) in clinical routine. However, few studies investigated this issue and the age-associated effects among large population in China. In this study, we aimed to figure out the age-associated utilization and in-hospital clinical outcomes of thrombus aspiration so as to improve therapeutic decisions in clinical routine. Methods: We retrospectively recruited 13655 eligible STEMI patients from the database of the Improving Care for Cardiovascular Disease in China-Acute Coronary Syndrome project. These subjects were allocated into primary percutaneous coronary intervention (PPCI)-only and thrombus aspiration groups after being subdivided into three age subgroups. The primary outcome was in-hospital cardiovascular death, and the key safety outcome was in-hospital stroke. Results: We observed that the ratio of STEMI patients undergoing thrombus aspiration to PPCI-only reduced with aging. For patients ≤ 75 years, the culprit lesion suffered from thrombus aspiration was mainly located in left anterior descending branch, and left-ventricular ejection fraction (LVEF) was lower and the rate of regional wall motion abnormality was higher in thrombus aspiration group (P<0.05). By contrast, for patients > 75 years, right coronary artery was the predominant culprit lesion undergoing thrombus aspiration, LVEF and the regional wall motion were comparable between two treatment groups. Thrombus aspiration neither reduced the in-hospital risk of cardiovascular death, all-cause death, recurrent myocardial infarction, acute stent thrombosis, heart failure, cardiogenic shock and sudden cardiac arrest nor increased stroke risk compared with PPCI-only group. However, after adjustment for age, thrombus aspiration presented the tendency to reduce the incidence of sudden cardiac arrest (4.9% vs. 2.5%, P=0.06) and in-hospital cardiovascular death at 3 days (hazard ratio 0.46; 95% CI, 0.20 to 1.06; log-rank P=0.08) in G76-95 group, and tended to increase the incidence of heart failure in G51-75 (5.7% vs. 6.9%, P=0.07). Conclusions: Thrombus aspiration neither significantly reduced the in-hospital incidence of major adverse cardiac events nor increased stroke risk. However, it might play a protective role in reducing in-hospital sudden cardiac arrest and increasing survival from cardiovascular death at 3 days for the elderly.